Hubungan Dukungan Sosial dengan Penyesuaian Diri pada Mahasiswa yang Berasal dari Papua di Universitas Negeri Padang - Amalia Rahmadhani; Salsabila Az-Zahra Rizal; Vevriyani Effendi; Mario Pratama (YASIN, 2026)
Although social support is considered to have an important role in the process of student adjustment, studies that specifically discuss the relationship between social support and the adjustment of students from Papua in the higher education environment remain limited. This study aims to determine whether or not there is a relationship between social support and the adjustment of students from Papua at Universitas Negeri Padang. This study employed a quantitative approach with a correlational design, involving 10 Papuan students as research participants. Data were collected through social support and adjustment questionnaires and were then analyzed using the Spearman-rho correlation test. The results showed a correlation coefficient of 0.431 with a significance value of 0.231, which means that there was no significant relationship between social support and adjustment. In addition, most students were in the moderate category for both variables. These findings indicate that social support is not the main factor affecting the adjustment of Papuan students at Universitas Negeri Padang. This study contributes to strengthening studies in educational psychology and cross-cultural student adaptation, while also providing practical implications that the adjustment of migrant students needs to be understood more comprehensively by considering factors other than social support.